Attention economy: understanding the new currency of business/ by Thomas H Davenport and John C Beck - Davenport, Thomas H.; Beck, John C. (Boston, 2001)
This title identifies attention management as the new critical competency for 21st century business. This is a landmark book for every manager who wants to learn how to earn and spend the new currency of business argues that unless companies learn to effectively capture, manage, and keep attention both internally and out in the marketplace, they'll fall hopelessly behind in our information-flooded world. It is based on an exclusive global research study, with examples from a range of companies. It provides a revolutionary four part model for managing attention in all areas of business. It presents a multidisciplinary approach to the topic of 'attention,' incorporating economics, psychology, and technology. It appeals to readers not only as representatives of an organization, but as individuals.
Keywords: Personal information management